Logistics Development and Trade Facilitation in Lao PDR - Arnold, John (World Bank, Washington, DC, 2014)
This report is part of a strategy to promotes trade competitiveness within the East Asia and Pacific Region. It presents an overview of the logistics issues facing East Asia countries and proposes a development agenda for them. Based on the recognition that the countries have basic differences in their level of development, extent of openness, and composition of trade, it begins by discussing the benefits of improved logistics. The East Asian countries are organized into an action matrix, with an analysis of the logistics needs appropriate to each group. The country working papers (volumes 2, 3, & 5)discuss the assessment of preset logistics services and the impediments they impose upon, and opportunities they offer for, expanded trade, including policy reform proposals. The special report on ports (volume 4) addresses port development in relation to urban growth.